Caracterização de minerais pesados ao longo do Rio Piranhas-Açu/RN: distribuição e proveniência - Silva, Marcia Gomes da (1999)
This dissertation deals with the characterization, distribution and provenience of heavy minerals along the Piranhas-Açu River, from the City of Parelhas (Seridó River) to your mouth at the City of Macau-RN. Many heavy minerals species were recorded in this study: clinoamphibole, epidote (including zoisite), garnet, sillimanite, tourmaline, staurolite, andalusite, zircon, rutile, augite, ilmenite, hematite and magnetite. Major transparent minerals, those forming more than 5% of some assemblages, are hornblende, epidote, tourmaline, staurolite and zircon. Predominant opaque mineral is ilmenite. Six assemblages were identified along the river: (i) Garnet-hornblende-tourmaline with sillimanite, when cutting rocks of the Seridó Formation; (ii) Hornblende-garnet-zircon, when crossing rocks of the Caicó gnaisse-migmatitic Complex; (iii) Hornblende-zircon-epidote-staurolite, when draining rocks of the Jucurutu Formation; (iv) Hornblende-zircon-epidote, when cutting rocks of the Açu Formation; (v) Hornblende-zircon-staurolite, on the lowermost Açu River, when crossing limestones of the Jandaíra Formation and (vi) Zircon-tourmaline-staurolite in the Açu River mouth (Cenozoic rocks) where coastal process dominate. Mineral ratios that reflect differences in grain shape, density, and selective chemical decomposition were used in an attempt to isolate the effects of source and process as controls of mineral variability. Reworking of the sediments was regionally effective in selective sorting; the more equant minerals (e.g. epidote) and heavier minerals (e.g. opaques) had a higher probability of being selected for permanent deposition during reworking. The processes of selective decomposition stand out at the river mouth. A priori knowledge of provenance, associated with the assemblage distribution and effects of process were utilized to the interpretations, that points to the follow provenances: hornblende comes from micashists of the Seridó Formation, orthognaisses and amphibolites of the Caico Complex, paragnaisses and paranphibolites of the Jucurutu Formation and granites intrusions; epidote comes from paragnaisses and calciosilicatics of the Jucurutu Formation, granites intrusions (-Npy3al/ca and -Npy3mz, gravels deposits and Açu Formation; Andalusite and staurolite come from the Seridó Formation; Sillimanite, tourmaline and garnet come from micashists of the Seridó Formation, as well as from quartzites of the Equador Formation; Zircon comes from Precambrian rocks (pink and prismatic zircon) and from sediments of several cycles (round zircon); Opaques come from all rocks cutted for the Piranhas-Açu River; Rutile comes from metamorphic rocks, in general; Augite comes from the Ceará-Mirim, Serra do Cuó and Macau volcanisms. The texture of gravels deposits reveals a sediment transport mechanisms by traction-current processes, together with a diagenetic clay matrix suggests a hot-humid environments for deposition. The presence of unstable heavy minerals assemblages, as well as pebbles of different composition and degrees of rounding and esfericity, indicate more than one source. The occurrence of calcio/alkaline granites suites, in areas closed to the gravel deposits, suggests that these intrusions are the main source of sediments. This could explain for instance, the significant amounts of epidote and presence of unstable heavy minerals (e.g. hornblende). The analyses of heavy minerals also show significante variability between the modern (Piranhas-Açu) and ancestral (Açu Formation) river sediments. In general, these variations reflect relatively higher unstable and lower stable heavy minerals contents of the modern Piranhas-Açu sediments. The absence of significant compositional differences probably reflects uniform weathering conditions